2022
DOI: 10.3390/cells11131998
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Induced Hepatocyte-like Cells Produced from Mesenchymal Stromal Cells: A Literature Review

Abstract: Liver disease is a leading cause of mortality worldwide, resulting in 1.3 million deaths annually. The vast majority of liver disease is caused by metabolic disease (i.e., NASH) and alcohol-induced hepatitis, and to a lesser extent by acute and chronic viral infection. Furthermore, multiple insults to the liver is becoming common due to the prevalence of metabolic and alcohol-related liver diseases. Despite this rising prevalence of liver disease, there are few treatment options: there are treatments for viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In addition to possessing hepatocyte-related functions, HLCs have been reported to exert inflammatory regulatory effects [ 37 ]. Therefore, we investigated the impact of HLCs supernatant on macrophage polarization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to possessing hepatocyte-related functions, HLCs have been reported to exert inflammatory regulatory effects [ 37 ]. Therefore, we investigated the impact of HLCs supernatant on macrophage polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Stem cell-derived HLCs are readily available with low immunogenicity. HLCs exhibit similar hepatic functions as primary hepatocytes and possess anti-inflammatory and regenerative effects [ [37] , [38] , [39] , 41 , 47 ]. Studies indicated that after hepatocyte differentiation, MSCs-derived HLCs gained hepatic functions including ALB formation, cytochrome P450 enzyme activity, urea secretion, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cirrhosis is a late-stage liver disease in which/ advanced stage of scaring and conditions, such as hepatitis and chronic alcoholism [1,2]. The liver carries out several necessary functions, including detoxifying harmful substances in your body, cleaning your blood, and making vital nutrients [3,4].…”
Section: Introductionmentioning
confidence: 99%